Perceived control over attitude: the psychological drivers of sustainable smart courses learning among economically disadvantaged undergraduates - Yun Zeng; Xiaokai Tang; Wen Jia (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2025)
Smart courses, being the effective tool for education equity, are faced with high dropout. This study investigates the factors affecting the complete of the smart courses of economically disadvantaged undergraduates from the psychology drive perspective. Nvivo tool was used to encode the screened 392 literature from Web of Science and the Engineering Index to explore the generic relationship among free nodes. According to the Theory of Planned Behavior, 17 hypotheses and corresponding Structural Equation Modeling were established, and 257 valid questionnaires（age of participants from 19 to 24）were collected for analyzing, and experts were invited to do an interview. The results indicated that behavioral attitude, subjective norms, and perceived behavioral control all had significant positive effects on students’ intention to engage in sustainable learning. Among them, perceived behavioral control demonstrated the strongest path coefficient (β = 0.499, p < 0.001), highlighting students’ self-efficacy and perceived resource controllability as key driving forces in promoting continuous learning. Although the effects of behavioral attitude (β = 0.343, p < 0.001) and subjective norms (β = 0.274, p < 0.001) were relatively weaker, the clarity of learning goals, expectations from others, and social support still played a positive role in motivating learning engagement. Different from the conventional view, this paper finds out that the most effective point is perceived behavioral control instead of attitudes for economically disadvantaged undergraduates for persistent learning behavior. This study provides a novel perspective on explaining economically disadvantaged undergraduates' sustainable smart courses learning behavior and offers practical recommendations to enhance course completion rates.